Actual tissue temperature during ablation index‐guided high‐power short‐duration ablation versus standard ablation: Implications in terms of the efficacy and safety of atrial fibrillation ablation. (6th November 2021) - Otsuka, Naoto; Okumura, Yasuo; Kuorkawa, Sayaka; Nagashima, Koichi; Wakamatsu, Yuji; Hayashida, Satoshi; Ohkubo, Kimie; Nakai, Toshiko; Hao, Hiroyuki; Takahashi, Rie; Taniguchi, Yoshiki
Abstract: Background: Actual in vivo tissue temperatures and the safety profile during high‐power short‐duration (HPSD) ablation of atrial fibrillation have not been clarified. Methods: We conducted an animal study in which, after a right thoracotomy, we implanted 6–8 thermocouples epicardially in the superior vena cava, right pulmonary vein, and esophagus close to the inferior vena cava. We recorded tissue temperatures during a 50 W‐HPSD ablation and 30 W‐standard ablation targeting an ablation index (AI) of 400 (5–15 g contact force). Results: Maximum tissue temperatures reached with HSPD ablation were significantly higher than that reached with standard ablation (62.7 ± 12.5 vs. 52.7 ± 11.4°C, p = 0.033) and correlated inversely with the distance between the catheter tip and thermocouple, regardless of the power settings (HPSD: r = −0.71; standard: r = −0.64). Achievement of lethal temperatures (≥50°C) was within 7.6 ± 3.6 and 12.1 ± 4.1 s after HPSD and standard ablation, respectively ( p = 0.003), and was best predicted at cutoff points of 5.2 and 4.4 mm, respectively. All HPSD ablation lesions were transmural, but 19.2% of the standard ablation lesions were not ( p = 0.011). There was no difference between HPSD and standard ablation regarding the esophageal injury rate (30% vs. 33.3%, p > 0.99), with the injury appearing to be related to the short distance from the catheter tip. Conclusions: Actual tissue temperatures reached with AI‐guided HPSD ablation appeared to be higher with a greater distance between the catheter tip and target tissue than those with standard ablation. HPSD ablation for <7 s may help prevent collateral tissue injury when ablating within a close distance.